Performance nutrition in the digital era - An exploratory study into the use of social media by sports nutritionists - Dunne, D. M.; Lefevre, C.; Cunniffe, B.; Tod, D.; Close, G. L.; Morton, J. P.; Murphy, R. (Journal of Sports Sciences, 2019)
This study aimed to explore how social media is being used by sports nutritionists as part of service provision, as well as practitioners` experiences and opinions of its use in practice. An exploratory sequential mixed methods approach was used during this research. Forty-four sports nutritionists completed an online survey detailing their personal and professional social media use. Semi-structured follow-up interviews were conducted with 16 participants who volunteered to do so. Survey responses were collated and reported as descriptive statistics. Interviews were thematically analysed.